FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI UNTUK MEMILIH PROFESI AKUNTAN PUBLIK (STUDI KASUS MAHASISWA PROGRAM STUDI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI) - Yudith Marshal; Marieta Ariani (EBID: Ekonomi Bisnis Digital, 2025)
This study aims to find out more deeply how personality, motivation, work environment and job market considerations influence accounting students' interest in choosing a public accountant profession. This study uses a quantitative method with an associative approach because it can test two or more variables. The population or sample of this study were active final year students of the Accounting Study Program, Trisakti University. Purposive sampling technique was used in the study to attract respondents who were distributed through google form, with a sample size of 156 respondents. Furthermore, the data was analyzed using SPSS (Statistical Package for Social Science) software. The results of this study indicate that the work environment and job market considerations have a positive and significant influence on accounting students' interest in choosing a public accountant profession. Meanwhile, personality and motivation do not have a significant influence on accounting students' interest in choosing a public accountant profession.